Родина Сигаревичів у процесі українського націєтворення наприкінці ХІХ – початку ХХ ст. - Музичко, О. (Чорноморська минувшина, 2012)
Метою статті є реконструкція внеску родини Сигаревичів, передусім Дмитра Дмитровича Сигаревича (1868 – 1914), у процес українського націєтворення наприкінці ХІХ – на початку ХХ ст. The purposes of this article are to create a historical portrait of Sygarevyches’ family, in particular, of Dmytro Dmytrovych Sygarevych (1868-1914), to give a definition of his place in the Ukrainian national movement, to make an analysis of his creative heritage. The conclusion is done, that D. Sygarevych was one of leaders of politicization process of the Ukrainian national movement. His living in Odesa, especially during 1905-1906 years, was the peak of his activity. D. Sygarevych was at the beginnings of the Ukrainian student’s movement in Odesa, he promoted to acquaintance of wide sectors of society with the Ukrainian culture. Целью статьи является создание просопографического исторического портрета семьи Сигаревич, прежде всего, Дмитрия Дмитриевича Сигаревича (1868 – 1914), в частности, определения его места в украинском национальном движении, анализ его творческого наследия. Сделан вывод, что Д. Сигаревич был одним из лидеров процесса политизации украинского национального движения. Пиком его деятельности было время его проживання в Одессе, особенно 1905-1906 гг. Д. Сигаревич стоял у истоков украинского студенческого движения в Одессе, содействовал ознакомлению широких слоев общества с украинской культурой.